Criticism of the Components of the Sufficiency Format in Kazem Al Yassin's Translation of the Novel "Qalb al-Lil" based on the Russian Approaches of Shveister and Retsker - Seyed Mahdi Nouri Keyzghani; Masoud Salmani Haghighi; Reyhaneh Hosseinabadi (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2022)
Linguistics deals with the study of language and provides solid and productive theories about how language works, and since translation is considered a linguistic activity, it is reasonable to imagine that linguistics can have something to say about translation. One of the techniques presented for translation is Schweitzer and Ratsker's Russian approach. This approach includes the components of the format of sufficiency or transformation of translation, which includes 4 elements of objectification, logical derivation, opposite translation, and compensation. In this essay, relying on the descriptive-analytical method, he criticized and examined the components of the sufficiency format in selected examples of Kazem Al Yassin's translation of the novel "Qalb al-Lil" based on Schweitzer and Ratsker's approaches, and at the end, the frequency of adherence to this pattern in the target language is displayed in two circular and column charts. The result of the research shows that the translator, in most cases, while respecting the style and components of the source text and its transmission, prioritizes the linguistic subtleties and expressive methods of the target text. Since translating all aspects of the original text, the structure and the message of the text is a difficult and possibly impossible task, so Kazem Al Yassin's effort to present a fluent text based on the components of the sufficiency format seems appropriate and acceptable.